Potential protective effects of polysaccharide extracted from Ulva lactuca against male reprotoxicity induced by thiacloprid. (20th October 2017) - Kammoun, Intissar; Bkhairia, Intidhar; Ben Abdallah, Fatma; Jaballi, Imen; Ktari, Naourez; Boudawara, Ons; Nasri, Moncef; Gharsallah, Neji; Hakim, Ahmed; Ben Amara, Ibtissem
Abstract: Context: Polysaccharides (PSs) from seaweeds have been reported to possess biological activity of potential medicinal values. Objective: The current study was conducted to establish the protective effects of PS extracted from Ulva lactuca against oxidative stress induced by Thiacloprid (THC) in the rat reproductive system. Materials and methods: Rats were exposed either to THC, THC + PS (100 mg/kg), or THC + PS (200 mg/kg). Results: Our study showed that THC induced severe disorders in the functional sperm parameters. A decrease in antioxidant activities and their genes expression were observed in the same group, compared to the controls. Our molecular data showing also a severe DNA breakdown in the testis of THC treated group. Moreover, THC treated group showed severe histopathological changes. Conclusions: Our results revealed that PS extracted from Ulva lactuca alleviated the THC induced reprotoxicity and reduced oxidative stress damages, DNA breakdown and histological injuries in the testis.